Sosialisasi Penerapan Internet of Things Menggunakan Arduino dan modul ESP 8266 Pada Karang Taruna Perum Tjitramas Residence - Thomas Afrizal; Han Sulaiman (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Internet knowledge and technology applications are learning that has recently been in great demand by all groups. no exception in the general public, especially youth organizations in housing or certain areas. This activity is a socialization in increasing the knowledge of youth organizations, especially in the Tjitramas Residence Parung housing complex. This aims to provide knowledge and skills to young people in terms of knowledge in the field of technology, especially Android, which is currently trending. In achieving the objectives of this activity, the implementing team uses the workshop method in a training event. The implementing team acting as tutors/instructors provides examples and at the same time provides assistance to training participants to master the training material. This allows participants to master the material while simultaneously practicing with instructor assistance. The results of this socialization, young people, especially the Tjitramas Residence youth organization, are very enthusiastic. This is because not only is the discussion trending, but many of them have an interest in the technology that is currently developing.